Revisiting the Genetic, Taxonomic and Evolutionary Aspects of Chagas Disease Vectors of the Triatoma phyllosoma Subcomplex (Hemiptera, Triatominae) - Cesaretto, Natália Regina [UNESP]; dos Reis, Yago Visinho [UNESP]; de Oliveira, Jader; Galvão, Cleber; Alevi, Kaio Cesar Chaboli [UNESP] (MDPI, 2022)
Triatoma bassolsae, T. longipennis, T. mazzottii, T. pallidipennis, T. phyllosoma and T. picturata are species that have great epidemiological importance in the transmission of Chagas disease in Mexico. However, there is no consensus regarding the specific status of these species, since they appear in various articles as species, subspecies and even subgenera. Thus, we revisited genetic, taxonomic and evolutionary data that allowed us to assess and discuss the specific status of these six species of the T. phyllosoma subcomplex. Phylogenetic studies were performed with nuclear (18S, 28S, ITS-2) and mitochondrial (16S, cytb, COI, COII, 12S) markers deposited in GenBank. In addition, data from experimental crosses were pooled and the genetic distance to the cytb gene was calculated. The phylogenetic reconstruction enabled us to rescue the six species as independent lineages. Post-zygotic reproductive isolation barriers (sterility and/or hybrid collapse) were observed for some experimental crosses. Although the other experimental crosses did not allow us to characterize reproductive barriers, these species showed high genetic distances in relation to the cytb gene (ranging from 4.6% to 14.9%). Thus, based on the revisited literature data, we confirmed the specific status of these six species of the T. phyllosoma subcomplex based on the phylogenetic and biological concepts of the species.
Keywords: experimental crosses; kissing bugs; phylogenetic systematics; triatomines